Evaluation of reported prostate cancer risk‐associated SNPs from genome‐wide association studies of various racial populations in Chinese men. Issue 15 (9th September 2013) - Na, Rong; Liu, Fang; Zhang, Penyin; Ye, Dingwei; Xu, Chuanliang; Shao, Qiang; Qi, Jun; Wang, Xiang; Chen, Zhiwen; Wang, Meilin; He, Dalin; Wang, Zhong; et al.
Abstract BACKGROUND Several genome‐wide association studies (GWAS) of prostate cancer (PCa) have identified many single nucleotide polymorphisms (SNPs) that are significantly associated with PCa risk in various racial groups. The objective of this study is to evaluate which of these SNPs are associated with PCa risk in Chinese men and estimate their strength of association. METHODS All SNPs that were reported to be associated with PCa risk in GWAS from populations of European, African American, Japanese, and Chinese descent were evaluated in 1, 922 PCa cases and 2, 175 controls selected from the Chinese Consortium for Prostate Cancer Genetics (ChinaPCa). A logistic regression analysis was used to estimate allelic odds ratios (ORs) of these SNPs for PCa. RESULTS Among the 53 SNPs, 50 were polymorphic in the Chinese population. Of which, 10 and 24 SNPs were significantly associated with PCa risk in Chinese men at P < 0.001 and <0.05, respectively. These 24 significant SNPs included 17, 5, and 2 SNPs that were originally discovered in European, Japanese, and Chinese descent, respectively. The estimated ORs ranged from 1.10 to 1.49 and the direction of association was consistent with previous studies. When ORs were estimated separately for PCa with Gleason score ≤7 and ≥8, a marginally significant difference in ORs was found only for two of the 24 SNPs (P = 0.02 and 0.04). CONCLUSION About half of PCa risk‐associated SNPs identified in GWAS of various populations are associated with PCa risk in Chinese men. Information on PCa risk‐associated SNPs and their ORs may facilitate risk assessment of PCa risk in Chinese men. Prostate 73: 1623–1635, 2013. © 2013 Wiley Periodicals, Inc.